2021
DOI: 10.1177/17411432211002517
|View full text |Cite
|
Sign up to set email alerts
|

Ethical dilemmas among mid-level school leaders through role-play simulations: Developing a social-ecological approach

Abstract: The purpose of the study is to examine the ethical dilemmas among mid-level school leaders in the social-ecological context through role-play simulations. We examined simulations involving role-played ethical scenarios and group debriefings among 30 mid-level school leaders from different Israeli high schools and districts during the MA course in the educational leadership program. A qualitative analysis generated an expanded social-ecological model for mid-level school leaders. The model consists of six main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Finally, based on the collective findings from different contexts concerning school principals' role in addressing the pandemic crisis, we can infuse through technology various simulation activities for future school principals. This particular aspect includes school principals' professional training programs that has already been introduced in the literature by research studies contributing to school principals' ethical dilemmas in school organizations (Iftach and Shapira-Lishchinsky, 2021; Shapira-Lishchinsky, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, based on the collective findings from different contexts concerning school principals' role in addressing the pandemic crisis, we can infuse through technology various simulation activities for future school principals. This particular aspect includes school principals' professional training programs that has already been introduced in the literature by research studies contributing to school principals' ethical dilemmas in school organizations (Iftach and Shapira-Lishchinsky, 2021; Shapira-Lishchinsky, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the findings from a study conducted in the USA in under resourced rural schools in Michigan indicated that school principals faced dilemmas that are related to educational policy issues (Kim & Lowery, 2021). In Israel, a study conducted from 30 mid-level school leaders from different districts concluded that school principals experienced ethical dilemmas from recurring tensions in caring for students and educators under their leadership, on one hand, and the need to follow formal rules, regulations, and professional standards, on the other (Iftach & Shapira-Lishchinsky, 2023). As emphasised by Arar and Saiti (2022), some of these dilemmas have clear legislation and guidelines, whereas others are characterised by uncertainty about how school principals should handle them.…”
Section: School Principals Face Ethical Dilemmasmentioning
confidence: 99%